Enzymatic conversion of pineapple plant stem starch and lignocellulosic materials into sugar syrups - Ramle, Illy Kamaliah; Jenol, Mohd Azwan; Ibrahim, Mohamad Faizal; Phang, Lai-Yee; Abd-Aziz, Suraini (Elsevier, 2024)
Managing pineapple waste amid increasing demand is crucial and repurposing this waste offers a sustainable solution. Pineapple stems, an overlooked resource rich in starch and lignocellulosic materials, were explored in this study. Enzymatic hydrolysis was used to convert the stems into sugar syrup. Optimal conditions resulted in a sugar concentration of 107.88 ± 1.56 g/L from 10% starch, using 1% (v/v) Dextrozyme and Celluclast 1.5 L. Hydrolysis was most efficient at 70 °C for starch and 40 °C for lignocellulose. The produced syrups match high fructose corn syrup (HFCS) in water activity, moisture content, and color, making them a promising alternative in food industry.